De-colonizing psychosocial science in the Kurdistan region of Iraq Examples from the Mastura Institute of Applied Science in Psychosocial Work - Karim, Ass. Prof. Dr. Luqman Saleh Karim; Mlodoch, Ass. Prof. Dr. Karin Mlodoch; Meintjes, Berenice Meintjes; Polla, Mam Polla; Gawlista, Kyra Gawlista (Sulaimani Journal for Humanities, 2026)
The Mastura Institute of Applied Science in Psychosocial Work has been established in 2023 in the Kurdistan Region of Iraq (KRI) as a non-University academic institute, which brings together University teachers, researchers, students and practitioners in the realm of psychosocial work, including psychosocial (activist) workers without formal education. The Institute has a strong emphasis on creative and grounded ways of facilitating training, supervision, research, internship, monitoring and evaluation, as well as in the engagement of practitioners and academics in conferences and exchange processes. The overall objectives include de-colonising knowledge transfer in the psychosocial sector, strengthening voices of local practices and knowledge in international knowledge debates, while establishing an equal platform of knowledge transfer and debate between West and East, North and South. Based on a series of workshops and discussions between Kurdish/Iraqi, South African and German academics and practitioners from multiple disciplines and work fields (Social Work, Psychology, Social Sciences, research, psychosocial counselling, etc.) on the contextualization of psychosocial knowledge, the paper examines the outcomes and dilemmas in systematizing local knowledge and creating in-depth exchange of theories and practice of psychosocial work across different contexts including challenges of language and translation. The paper is based on a qualitative, evaluative research, conducting in-depth, individual and focus group discussions with participants of reflective workshops and activities at the Mastura Institute. The paper contributes to the broader debate on how to put decolonial approaches to knowledge production and exchange in the fields of Social Work, Psychology and Social Sciences into practice.
Keywords: Decolonization; Knowledge Production; Psychosocial Work; Local knowledge; Mastura Institute